Digital business: a way forward for inclusive growth - Khaliq, Ahmad (2019)
Digital Business is a way forward in this century where every thing is becoming virtual. This conference and panel discussion was organized to focus on the benefits and challenges of modern technology such as AI (Artificial Intelligence) that make certain business to disappear and new form of digital business emerged. This has serious implications for business today with an emerging opportunities.